Data Accessibility Model Using QR Code For Lifetime Healthcare Records - Leza, F. N. M.; Nurul A., Emran; Ghani, M.K. A. (2013)
One factor that determines the quality of healthcare services is the accessibility of patient records. Fast and seamless access to patient records is necessary in order to support sharing of complete lifetime patient records among healthcare providers while promoting the greater use of it. Nevertheless, studies on how complete lifetime patient record can be acquired by improving the way these records are accessed are limited. In this paper, the conceptual model of data accessibility in healthcare domain will be presented. QR code technology will be adopted in the model as a tool that enables multi-platforms data access points. Incremental data updates will be used as a mean to share complete, up-to-date lifetime patient records. Software prototype architecture and the interface design of the model will be also presented in this paper. The contribution of the work is on improving lifetime patient records accessibility that consequently promotes sharing of complete patient records among healthcare providers.